Shaping the Black Sea Region’s Image in the XIX Century: Imperial Alternative - Казанков, Роман (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2019)
The article is devoted to the highlighting of the particularities of the process of creation of the Black Sea region’s image. Stepwise examination and depiction of the Black Sea territories has been analyzed. The process of formulation of the region’s basic characteristics during the XIX century has been discovered. Establishment of the institutional network for the discovering of new lands has been revealed. Special attention is paid to the A. Skalkovskiy’s papers which are reflect the main thesis of the Black Sea region’s image in Russian scientific and socio-political discourses.